Liver Metabolome and Proteome Response of Turbot (Scophthalmus maximus) to Lysine and Leucine in Free and Dipeptide Forms - Wei, Yuliang; Li, Benxiang; Xu, Houguo; Liang, Mengqing (Frontiers in Marine Science, 2021)
Omics approaches provide more metabolic information to explain the relationship between dietary nutrition and fish growth. This study aimed to explore the metabolome and proteome response of turbot (Scophthalmus maximus) fed diets containing lysine and leucine in free and dipeptide forms by the approaches of integrated liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based metabolomics and isobaric tags for relative and absolute quantification (iTRAQ)-based proteomics. Plant protein based diets were formulated to contain the equivalent of lysine and leucine in free amino acid (crystalline amino acid, CAA) and synthetic Lys-Leu (Lys-Leu) forms. Metabolome and proteome profile of liver were screened in fish fed either the CAA diet or the Lys-Leu diet after an eight week feeding trial. Fish fed the Lys-Leu diet showed significantly higher final body weight and specific growth rate compared with fish fed the CAA diet. Protein and amino acid related - metabolic processes in liver were identified between the Lys-Leu and CAA groups based on differential metabolites and proteins. Proteolytic enzymes and amino acid transporters from differential proteins of liver showed that the process of protein digestion and absorption may be affected by different forms of lysine and leucine in feed. Mechanistic target of rapamycin complex 1 and ubiquitin proteasome pathways were identified by differential proteins, which were involved in the processes of protein synthesis and degradation in liver. Lysine degradation, tryptophan metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis, arginine and proline metabolism, and glycine, serine and threonine metabolism were identified based on differential metabolites and proteins, which showed that the metabolism of various amino acids including lysine had been affected by both the CAA and Lys-Leu groups. In conclusion, the data of integrated metabonomics and proteomics suggested that the mechanism of the effects of dietary lysine and leucine on the growth of turbot can be understood in protein and amino acid related - metabolic processes of liver from three aspects: protein digestion and absorption, protein synthesis and degradation, and amino acid metabolism. In addition, a good correlation between differential metabolites and proteins was observed by using the approaches of integrated LC-MS/MS-based metabolomics and iTRAQ-based proteomics.